Analysis of Tuan Tewo Traditional Ceremony in Samparong Village, Sikka Regency - Sarnia; Mayaputri, Velmi; Naro, Antonius M. K. (The Indonesian Institute of Science and Technology Research, 2024)
Traditional ceremonies are one of the traditions of indigenous peoples that are considered to still have values that are quite relevant to the needs of the supporting community. In addition to being a human effort to connect with the spirits of ancestors, it is also a form of human ability to actively adapt to nature or the environment in a broad sense. This research aims to analyze one of the traditional ceremonies in Indonesia, especially in Samparong Village, Sikka Regency. The traditional ceremony is called Tuan Tewo. The researcher uses qualitative methods. The data collection techniques used in this research are interviews and documentation. The results discuss several stages in the Tuan Tewo ceremony process. Tuan Tewo ceremony process has two stages, namely the ritual preparation stage and the implementation stage. In addition, this research found Samparong community perspectives towards the Tuan Tewo traditional ceremony in Samparong Village, where the Tuan Tewo traditional ceremony is only a form of preserving their culture and customs left by their ancestors. The impact of not implementing the Tuan Tewo traditional ceremony is that this is quite old ancestral heritage and various bad things hit the farmers' crops. Therefore, the Samparong community in Sikka Regency has to maintain the tradition of the Tuan Tewo ceremony as an expression of community identity. The local government should be able to continue mobilizing the community to be actively involved in the preservation of Tuan Tewo's traditional ceremony. In addition, it is also hoped that the government will include all traditions carried out by local communities in an educational aspect.